2019
DOI: 10.20944/preprints201908.0132.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schizophrenia Phenomenology Comprises a Bifactorial General Severity and a Single-group Factor, Which Are Differently Associated with Neurotoxic Immune and Immune-regulatory Pathways

Abstract: In schizophrenia, a single latent trait underlies psychosis, hostility, excitation, mannerism, negative (PHEMN) symptoms, formal thought disorders (FTD) and psychomotor retardation (PMR).Schizophrenia is accompanied by a breakdown of gut and blood-brain-barrier (BBB) pathways, increased tryptophan catabolite (TRYCAT) levels, bacterial translocation, and lowered natural IgM and paraoxonase (PON)1 activity.The aim of this study was to examine the factor structure of schizophrenia symptom domains and the biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…on the 6 OS variables (even without FDR correction). In previous studies using the same study sample we showed that there were no significant effects of the drug state on the other biomarkers listed in table 1 [4,11]. Table 4 shows significant logistic regression models predicting deficit schizophrenia using different biomarkers sets.…”
Section: Ostox and 3antiox In Deficit And Non-deficit Schizophreniamentioning
confidence: 79%
See 3 more Smart Citations
“…on the 6 OS variables (even without FDR correction). In previous studies using the same study sample we showed that there were no significant effects of the drug state on the other biomarkers listed in table 1 [4,11]. Table 4 shows significant logistic regression models predicting deficit schizophrenia using different biomarkers sets.…”
Section: Ostox and 3antiox In Deficit And Non-deficit Schizophreniamentioning
confidence: 79%
“…Moreover, these OSTOX/ANTIOX biomarkers explained a large part of the variance in a general factor extracted from the symptom domains and neurocognitive tests, reflecting OSOS. As reported previously, this single latent trait is essentially unidimensional and underpins the key domains of schizophrenia which are, therefore, manifestations of this common underlying construct [4][5][6]36]. This latent OSOS factor, which reflects the late phenome of schizophrenia, indicates disorders in neuronal circuits including in the "prefronto-striato-thalamic, prefrontoparietal, prefronto-temporal, and dorsolateral prefrontal cortex, as well as hippocampus and amygdala" [4,5,81,82].…”
Section: Sh-disulphide Homeostasis Ismentioning
confidence: 85%
See 2 more Smart Citations
“…Schizophrenia is a chronic mental illness affecting around 1% of the world population (Janoutová et al, 2016). Schizophrenia is characterized by a symptomatome (defined as the aggregate of symptoms) comprising psychotic symptoms, hostility, excitation, mannerism (PHEM), negative symptoms, psychomotor retardation (PMR), and formal thought disorders (FTD) (Maes et al, 2019b;Almulla et al, 2020b;Maes et al, 2020b). In fact, the symptomatome of schizophrenia should be conceptualized as a single latent trait extracted from all those symptom domains, which reflect overall severity of symptoms of schizophrenia (OSOS) (Maes et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%